Modern Irish Autobiography Self, Nation and Society - Harte, L.; Harte, L. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2007)
Modern Irish Autobiography provides the first comprehensive critical analysis of the Irish autobiographical tradition from the early nineteenth century to the present day. This pioneering collection offers readers a stimulating and provocative introduction to the principal themes, modes and narrative strategies of Irish autobiographers.